The neglected health needs of older Syrian refugees in Jordan - Lupieri, S (Refugee Studies Centre, University of Oxford, 2018)
Older refugees are often a neglected population, particularly when it comes to health. In Jordan, the specific health needs of older Syrian refugees tend to be overlooked, due in part to a lack of data, institutional biases and the nature of the humanitarian response.